Sorry I don’t know the answer hope you find one bye
Answer:
x = 1 1/4
Step-by-step explanation:
sqrt( 7x+2) = sqrt(3x+7)
Square each side
(sqrt( 7x+2))^2 = (sqrt(3x+7))^2
7x+2 = 3x+7
Subtract 3x from each side
7x-3x +2 = 3x+7-3x
4x+2 = 7
Subtract 2 from each side
4x+2-2 = 7-2
4x = 5
Divide by 4
4x/4 = 5/4
x = 1 1/4
Check for extraneous solution
sqrt( 7*5/4+2) = sqrt(3*5/4+7)
sqrt( 35/4 + 8/4) = sqrt(15/4+28/4)
sqrt( 43/4) = sqrt(43/4)
Solution is valid
Given:
and
where
.
To find:
The explicit formula for the given recursive formula.
Solution:
We know that recursive formula of an AP is:

Where, d is the common difference.
We have,

Here, d=9.
The first term of the AP is
.
The explicit formula for an AP is:

Substituting
and
, we get



Therefore, the required explicit formula for the given sequence is
.
Answer:
2
Step-by-step explanation:
|-6+8|
Add/subtract the numbers: -6 + 8 = 2
= |2|
Apply the absolute value rule: |a| = a, a ≥ 0
= 2